2018
DOI: 10.1186/s12889-018-5448-z
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference may be a valuable tool for screening individuals with obesity: findings from a young Chinese population and a meta-analysis

Abstract: BackgroundCentral obesity and overweight/obesity can result in various chronic non-communicable diseases, such as cardiovascular disease, metabolic syndrome, and diabetes mellitus. Waist circumference (WC) and body mass index (BMI) are widely used to measure obesity despite their limitations. For example, WC and BMI cannot be measured in pregnant women and subjects with abdominal ascites or masses. Therefore, this study aims to determine the efficacy of neck circumference (NC) as a tool for screening central o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…[ 14 ] However, both of these methods are not without their limitations for example in cases of abdominal ascites, masses or in athletes. [ 15 17 ] More recently, NC has been recognized as tool for assessing overweight and obesity in adults, although its usefulness for screening individuals with central obesity is less clear. [ 17 ] Two studies of Saudi adults have demonstrated the NC correlates with WC and BMI, and can be used to screen for overweight and obesity, as well as being culturally acceptable when performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] However, both of these methods are not without their limitations for example in cases of abdominal ascites, masses or in athletes. [ 15 17 ] More recently, NC has been recognized as tool for assessing overweight and obesity in adults, although its usefulness for screening individuals with central obesity is less clear. [ 17 ] Two studies of Saudi adults have demonstrated the NC correlates with WC and BMI, and can be used to screen for overweight and obesity, as well as being culturally acceptable when performed.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 17 ] More recently, NC has been recognized as tool for assessing overweight and obesity in adults, although its usefulness for screening individuals with central obesity is less clear. [ 17 ] Two studies of Saudi adults have demonstrated the NC correlates with WC and BMI, and can be used to screen for overweight and obesity, as well as being culturally acceptable when performed. [ 18 , 19 ] However, 2 recent meta-analyses/systematic reviews have reported that NC has moderate accuracy for identifying overweight and obesity in children and adolescents, although the issues of standardization of measurements and cut-off values by age and gender remain.…”
Section: Introductionmentioning
confidence: 99%
“…Cut off value in Chinese for overweight/obesity was 37.4 cms and 32.2 cms and, for central obesity 37.1 cms and 32.6 cms in males and females respectively. 5 In a study by Jagadamba et al, NC ≥36 cm in diabetics and ≥37 cm in non-diabetics was the best cut off value to determine subjects with central obesity. 6 Study by…”
Section: Discussionmentioning
confidence: 93%
“…In recent years, with the rapid development of the economy and the increased aging population, the incidence of chronic non-communicable diseases has grown higher and higher, especially in terms of diabetes, high blood pressure, hyperlipidemia, hyperuricemia, obesity, and chronic psychological stress. Stress can specifically lead to the occurrence of atherosclerosis, and the problem is becoming more and more serious [ 12 , 13 ]. In the process of atherosclerosis, there are changes in vascular intima and media thickness.…”
Section: Discussionmentioning
confidence: 99%